1999
DOI: 10.1159/000027412
|View full text |Cite
|
Sign up to set email alerts
|

Primary Orbital Leiomyoma and Leiomyosarcoma

Abstract: A case of an extremely rare primary orbital leiomyoma in a 25-year-old male patient is presented who had a lifelong history of deviation of the left eye globe with slight enophthalmos and reduced motility. Because of pain and increasing deviation of the eye the tumor was totally resected. On histologic examination the tumor showed ossification which is extremely rare so that a calcifying fibroma had to be ruled out. In immunohistochemistry, however, this tumor stained with smooth muscle antigen. Less than 2% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
0
27
0
4
Order By: Relevance
“…Highest prevalence is seen in the 4th and 5th decades of life with slight male predilection [13] (1.43:1). However, few reports suggest slight female predominance of leiomyomas in the head and neck region and the authors attribute it to hormonal variation, i.e., progesterone receptor positive and estrogen receptor negative on immunochemical studies [14,15]. Although most of these lesions are asymptomatic, few authors reported symptomatic lesions that are associated with pain, tooth mobility, difficulty in chewing and swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Highest prevalence is seen in the 4th and 5th decades of life with slight male predilection [13] (1.43:1). However, few reports suggest slight female predominance of leiomyomas in the head and neck region and the authors attribute it to hormonal variation, i.e., progesterone receptor positive and estrogen receptor negative on immunochemical studies [14,15]. Although most of these lesions are asymptomatic, few authors reported symptomatic lesions that are associated with pain, tooth mobility, difficulty in chewing and swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…A search of MEDLINE (1966-2009) using the key words ''retroperitoneal leiomyosarcoma'' and ''orbit'' produced 28 citations; however, no report of orbital metastasis of a retroperitoneal leiomyosarcoma was found. In nine cases, leiomyosarcomas originated from the orbit [2][3][4][5][6][7]. In six cases, orbital leiomyosarcomas occurred after high-dose radiation therapy for retinoblastoma [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, only 15 well-documented cases of orbital leiomyoma have been reported in the English-language medical literature. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] The diagnosis of orbital leiomyoma was confirmed by immunohistochemistry in only 4 of these 22 reported cases. We reviewed 4 cases of orbital leiomyoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, intracranial extension 5,14 and extension in paranasal sinuses have been reported. 12 Orbital CT usually shows a well-circumscribed orbital mass. Although MRI was used previously in 2 cases, 12,13 the imaging characteristics have not been well documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation